Examining the role of well-being in the marketing discipline - Perrewé, Pamela L.; Harms, Peter D. (Research in occupational stress and well being, 2019)
Volume 17 of Research in Occupational Stress and Well Being is focused on the stress and well-being related to the marketing discipline. This volume is focused on the connections between employee stress, health, and well-being as it relates to marketing, sales, and customers. We have 7 chapters devoted to critical topics such as internal selling, stress at the consumer-employee interface, how leaders can affect the customer experience, and the unique stressors associated with being a persuasion agent. Further, we have two comprehensive empirical reviews of topics in this domain. The first examines the degree to which positive psychology constructs relate to sales performance. The second examines customer mistreatment towards employees and how it impacts their well-being. The final chapter takes a more practitioner perspective and examines the importance of taking into account stress tolerance when selecting and training sales personnel. The objective of this series is to promote theory and research in the increasingly growing area of occupational stress, health and well-being, and in the process, to bring together and showcase the work of the best researchers and theorists who contribute to this area. Questions of work stress and well-being span many disciplines and many specialized journals. One of the virtues of this series has been to provide a multidisciplinary and international platform that gives a thorough and critical assessment of knowledge, and major gaps in knowledge, on occupational stress and well-being.